Metallic glasses–novel materials for applications in nuclear fusion - Stiehler, Martin E.; Georgarakis, Konstantinos (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Novel alloys like metallic glasses (MGs) hold the potential to revolutionize many scientific and industrial sectors including nuclear fusion (NF). These metallic materials with amorphous atomic structure possess outstanding mechanical properties in combination with high corrosion resistance and high radiation tolerance. They can be made and shaped in unique ways impossible for conventional crystalline materials. MGs also offer high compositional flexibility and can be tailored to various specific applications. Here, we give a brief overview on how the fusion sector can benefit from MGs and, as examples, highlight some specific use cases. We also outline a pathway for the future development of MGs specifically designed for the extreme environments occurring in NF.
Keywords: 5106 Nuclear and Plasma Physics; 51 Physical Sciences; Fluids & Plasmas; 5106 Nuclear and plasma physics; Amorphous materials; casting; corrosion resistance; metallic glasses (MGs); novel alloys; nuclear fusion (NF); radiation tolerance; radio frequency (RF) antenna; sputtering; structural materials